(untitled) (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
In an effort to produce a quality generation both in terms of academics and morality, the curriculum needs to be designed and developed in accordance with the conditions or problems faced by students and their environment. This research aims to explore the design of Islamic religious education curriculum development that focuses on relevant issues. This choice is interesting because it is based on the assumption that humans as social beings must be faced with problems in life that require a common solution to be resolved. This research uses the library research method, by studying various articles, books, proceedings, and research related and relevant to the research topic as a reference. The results of this study indicate that problem-centered curriculum development design can improve students’ critical thinking skills, social skills, self-confidence, and learning outcomes in understanding and solving social problems in society related to Islamic values education. Therefore, educators need to develop a problem-centered curriculum design in learning Islamic education. The purpose of this design is to make learning easier for students to understand because it is closely related to the lives they experience in the school and community environment.